Clinical profile of hypernatremic dehydration in term neonates - Jayaprakash, Renu Prakash Nagappa; Rao, Uday Kumar Seetharam; Sanikam, Hareesh (International Journal of Contemporary Pediatrics, 2025)
Background: Hypernatremic dehydration in neonates is a common situation, particularly in developing countries. Signs and symptoms of hypernatremic dehydration in neonates are subtle and non-specific. The clinical features at presentation are lethargy, poor feeding, reduced urine output, excessive weight loss, and in some cases seizures. Early breast feeding, counselling of mothers regarding breast feeding, monitoring of neonates with excessive weight loss and prompt correction of hypernatremia can prevent complications like acute kidney injury (AKI) and intraventricular haemorrhage. Methods: The present study is a descriptive cross-sectional study conducted at department of pediatrics, ESIC-MC and PGIMSR between August 2022 to January 2024. A total of 78 neonates were enrolled. Results: The male: female ratio was 1.2:1. Majority of neonates were born to primi gravidas and delivered through LSCS. The most common symptom was poor feeding followed by reduced urine output, lethargy and fever. Most of the neonates had mild hypernatremia and most common associated complication was AKI. None of the neonates had severe hypernatremia or seizures. Conclusions: Early diagnosis and treatment of hypernatremic dehydration is of paramount importance to prevent morbidity and mortality. Early initiation of breast feeding and monitoring for excessive weight loss, counselling of mothers to identify at risk neonate is important in prevention and diagnosis of hypernatremic dehydration.